Physical modelling of wave propagation and wave breaking in a wave channel - Neves, D. R. (2012)
The presented work describes a wide range of wave channel tests performed at the National Laboratory of Civil Engineering (LNEC), considering different incident wave conditions, with the objective of studying the wave breaking hydrodynamics. Special attention was made to the end of the wave breaking process. The experimental setup, the incident wave conditions, the equipment and the performed measurements (free surface elevation and particle velocity) are herein described. Time, spectral and statistical analysis based upon the measured data are also performed and presented. Moreover, a more deepen analysis related: (i) the relative wave height (H/d); (ii) the wave celerity; (iii) the two-dimensional distribution of the particle velocities components in the xy, xz and yz planes and; (iv) the average wave direction and spreading angle is carried out and presented. Vertical velocity profiles are also presented.